DÜRZiliGiN TEMEL KAYNAKLARI: DÜRZi RiSALELERi - Bağlıoğlu, Ahmet (Fırat University, 2003)
That Hamza b. Ali wrote the epist/es with that et-Temimi and Muktend Bahdeddin wrote ones were carachteri
Keywords: Religious Studies; Din Araştırmaları